Complement Inhibition in ANCA-Associated Vasculitis - Tesar, Vladimir; Hruskova, Zdenka (Frontiers in Immunology, 2022)
Efficacy of immunosuppressive treatment of ANCA-associated vasculitis (AAV) is complicated by its toxicity. With the replacement of cyclophosphamide with rituximab serious adverse events seem to be associated especially with high-dose corticosteroids. Activation of alternative complement pathway plays an important role in the pathogenesis of AAV. Avacopan (C5a receptor inhibitor) was demonstrated to have at least similar efficacy and better safety compared to high-dose corticosteroids in the induction treatment of AAV. Other modes of the inhibition of alternative complement pathway are currently tested in AAV or could be considered based on the experience in other glomerular diseases.